Validity of parameters in static linear testing of flexor tendon repair. Issue 13 (6th September 2016) - Linnanmäki, Lasse; Göransson, Harry; Havulinna, Jouni; Sippola, Petteri; Karjalainen, Teemu; Leppänen, Olli V.
Abstract: To study the biomechanical properties of flexor tendon repairs, static tensile testing is commonly used because of its simplicity. However, cyclic testing resembles the physiological loading more closely. The aim of the present study is to assess how the biomechanical competence of repaired flexor tendons under cyclic testing relates to specific parameters derived from static tensile testing. Twenty repaired porcine flexor tendons were subjected to static tensile testing. Additional 35 specimens were tested cyclically with randomly assigned peak load for each specimen. Calculated risks of repair failure during repetitive loading were determined for mean of each statically derived parameter serving as a peak load. Furthermore, we developed a novel objective method to determine the critical load, which is a parameter predicting the survival of the repair in cyclic testing. The mean of statically derived yield load equalled the mean of critical load, justifying its role as a valid surrogate for critical load. However, regarding mean of any determined parameter as a clinically safe threshold is arbitrary due to the natural variation among samples. Until the universal performance of yield load is verified, we recommend employing cyclically derived critical load as primary parameter when comparing different methods of flexor tendon repair.